Nasionalisme Dan Budaya Di Indonesia Dalam Masyarakat Risiko - Hafizh Ahmad Fajar Rizal Hadi; Zulfatuz Zakiyah; Izatil Hidayah Sajidah (Universitas Maritim AMNI Semarang, 2023)
In every human life that is constantly changing from time to time has made the existence of risk a determinant of how life in the future will occur. Ulrich Beck discovered the concept of a risk society that is closely related to industrial society. This concept discusses modernity which has consequences or risks related to technological advances and globalization. Modernity creates global risks where each of these risks was previously unknown to society. Developing countries are vulnerable countries in the dynamics of globalization compared to developed countries. This is because developing countries do not yet have sufficient capacity to regulate their own country. Therefore it is necessary to understand the risks of what is being done now by studying the past and analyzing the present life for a better life in the future. This study used a qualitative research method with a descriptive narrative study approach. The purpose of this research is to understand the importance of understanding the risks of every action, especially in the modernity of technological development and globalization so that future conditions can run in a sustainable manner.